IMPLEMENTASI NILAI PANCASILA DALAM KEHIDUPAN SOSIAL DAN BUDAYA DI DUSUN SADE DESA REMBITAN - Lalu Gede Angga Pratama; Rullian Hidayat; Baiq Tiara Putri Fajriat; Firda Andini; Siti Azkiyatul Fikri; Wafiq Azizatun Munawwaroh; Olivia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Pancasila is the collective soul of the Indonesian people, providing life to the state and guiding society toward justice and prosperity. This research examines the application of Pancasila's values in the daily lives of the Sasak community in Dusun Sade, Rembitan Village, a culturally rich area facing challenges of modernization and globalization. Employing a qualitative approach with descriptive methods, the study aims to explore how Pancasila principles, such as social justice, mutual cooperation, and consensus-building, are internalized and practiced in resolving social conflicts while preserving local traditions. The findings reveal the significance of integrating Pancasila into cultural practices to maintain social cohesion and strengthen cultural identity. The research offers theoretical insights into the relevance of Pancasila in diverse local contexts and practical recommendations for policy development to support cultural preservation and social harmony. This study highlights the importance of balancing cultural heritage with modern influences to foster a united and harmonious society.